2018
DOI: 10.5812/archcid.61012
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Epidemiologic, Laboratory, and Clinical Features of Brucellosis Patients Hospitalized in the North of Iran During 2009 - 2014

Abstract: Background: Brucellosis is a zoonosis with diverse clinical manifestations. This study investigated the epidemiological, laboratory, and clinical features of brucellosis. Methods: In a cross-sectional survey, we evaluated brucellosis patients who referred to Razi hospital, a referral center for infectious diseases in Mazandaran province (north of Iran), from 21 March 2009 to 20 March 2014. Factors such as age, sex, clinical signs, and laboratory findings were extracted from their medical records. Results: 219 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
4
3
0
2
Order By: Relevance
“…The incidence of the disease shows a seasonal pattern in Iran so that it increases in spring and summer (because of mating and breastfeeding of livestock) and then decreases (14). The epidemiological findings of the present study are consistent with previous research (15)(16)(17)(18). The present results showed that the frequency of brucellosis was higher in men and the age group of 20 -40 years.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of the disease shows a seasonal pattern in Iran so that it increases in spring and summer (because of mating and breastfeeding of livestock) and then decreases (14). The epidemiological findings of the present study are consistent with previous research (15)(16)(17)(18). The present results showed that the frequency of brucellosis was higher in men and the age group of 20 -40 years.…”
Section: Discussionsupporting
confidence: 91%
“…Бруцельоз є однією з найбільш поширених зоонозних інфекцій в світі з високим відсотком хронічних форм, що відповідно негативно впливає на економічну складову систем охорони здоров'я країн з високою поширеністю бруцельозу [7]. Одні з найвищих показників захворюваності на бруцельоз спостерігаються в країнах Центральної Азії і Східної Європи [3,4].…”
Section: вступunclassified
“…Бруцельоз є поширений серед усіх вікових груп, хоча в більшості випадків вражається молодий, працездатний прошарок населення, що підтверджується даними цілої низки дослідників [1,6,9]. В інших працях було відмічено, що бруцельоз частіше зустрічається серед пацієнтів старшого віку [2,7]. Статевий розподіл серед наших хворих, а саме переважання осіб чоловічої статі (75,00%) співпадає з даними більшості дослідників [10,12], що можливо пов'язано з найбільш широким залученням чоловіків до роботи з тваринами та вживанням необробленої продукції тваринництва.…”
Section: результати обговоренняunclassified
“…Brucellosis is one of the most common zoonotic infections in the world, annually there are about 500 thousand new cases [1,2]. Despite the wide spread of this infection in the world, there are areas with a pronounced endemic for brucellosis.…”
Section: Introductionmentioning
confidence: 99%